Réponses

2014-04-12T13:59:48+02:00




bonjour
Q = (2+x)(2x+5)-(2-x)(2+x)

1. Développer et réduire Q.
Q = 4x² +10 +2x² +5x - (4 +2x -2x -x²)
Q = 6x² + 5x +10 - 4 +x²
Q = 7x² + 5x +6

2.Favoriser Q.
Q = ( 2+x)( 2x+5 - 2 +x)
Q = (2 +x)( 3x +3)

3.Resoudre l'équation Q=0.

soit 2 +x = 0 et x = -2
soit 3x +3 = 0 donc 3x = -3 et x = -1
desoler au début javais mis une reponse de probléme
2014-04-12T14:00:10+02:00
Bonjour
Q = (2+x)(2x+5)-(2-x)(2+x)

1. Développer et réduire Q.
Q = 4x² +10 +2x² +5x - (4 +2x -2x -x²)
Q = 6x² + 5x +10 - 4 +x²
Q = 7x² + 5x +6

2.Favoriser Q.
Q = ( 2+x)( 2x+5 - 2 +x)
Q = (2 +x)( 3x +3)

3.Resoudre l'équation Q=0.

soit 2 +x = 0 et x = -2
soit 3x +3 = 0 donc 3x = -3 et x = -1